+0  
 
0
108
2
avatar

i tried -8 and it was wrong...

 

here’s my work.... i am going to make my work neater next time😐

 

 

 

Maybe you can just point out the mistake I made only...

 Oct 20, 2018
 #1
avatar+98044 
+1

x * y   =  ( x + 2) (  y - 3)

 

So

 

t * ( t + 2)  =

 

(t  + 2) * [(t + 2) - 3 ]  = 

 

( t + 2) ( t - 1)

 

t^2 + t - 2    (1)

 

  And 

 

(t + 1) ( t + 1)  =

 

[ ( t + 1) + 2 ]  *  [ ( t + 1) - 3 ]  =

 

( t + 3) ( t - 2)  = 

 

t^2 + t -  6     (2)

 

So

 

(1)  - (2)  =

 

[ t^2 + t  - 2 ]  - [ t^2 + t - 6 ]  =

 

4

 

 

cool cool cool

 Oct 20, 2018
edited by CPhill  Oct 20, 2018
 #2
avatar
0

I got it right the first time!!! :( I got -8 when I went back and check my work... I guess I should never go back and check my work again?

Guest Oct 20, 2018

35 Online Users

avatar
avatar
avatar